開心術後の急性じ不全の臨床的検討 - ENDO Y.; IGARI T.; KONNO O.; TERANISHI Y.; HANEDA K.; ABE T.; USUBA A.; INOUE H.; SHOJI M.; HOSHINO S.; MOTOKI R.; HONDA K. (Jinko Zoki, 1984)
Out of 696 cases of open heart surgery, 20 (2.9%) cases had postperative acute renal failure. Since 1978, we have employed the following diagnosis, management and therapy. 1) early detection by free water clearance 2) hemodynamic management using Swan-Ganz catheter 3) early therapy by large doses of diuretics and dialysis 4) administration of dopamine and performing of IABP for low output syndrone. As a result we improved survival vate from 23% in the early term to 43% in the late term. 教室における開心術696例のうち, 急性腎不全の発生をみた20例(2.9%)を前期(S. 46.5～S. 52.12)と後期(S. 53.1～S. 57.12)に分けて検討したところ, 前期より後期に術前腎機能障害を有する症例が多く, 体外し循環もより長時間であり, 心疾患の重症化が示唆された。腎不全の救命率は, スワンガンッカテーテルたよる管理下で, 自由水クリアランスによる早期発見, 利尿剤大量療法無効時の早期透析により, また低心拍出量症候群に対してはドパミンやドブタミンや大動脈内バルーンパンピング法による血行動態の是正により, 前期23%より後期43%に改善し, 昭和57年には4例中3例(75%)救命し得た。急性腎不全の発生率は, 心筋保護の導入, 体外循環や術前・術後管理の向上などにより, 前期4.1%より後期1.9%に改善された。